Hepatocyte growth factor stimulates neutrophil degranulation but not respiratory burst - I. C. Kowanko; A. Ferrante; T. Nakamura (Mediators of Inflammation)
Neutrophil function is regulated in part by cytokines with growth factor activities for different cell types. Hepatocyte growth factor (HGF) is a cytokine produced during injury to the liver and other organs. Neutrophils are numerous in such tissue injury sites and may be influenced by HGF. In the present study the effect of HGF on neutrophils was investigated. The data show that HGF at 1–10 ng/ml increased lysosomal enzyme release from both specific and azurophilic granules of cytochalasin-B treated neutrophils. The release of specific granule contents in response to N-formyl-methionyl-leucylphenylalanine was also increased by HGF. In contrast there were no significant effects of HGF on neutrophil respiratory burst, adherence or locomotion. It is concluded that HGF modulates neutrophil granule exocytosis.